2021
DOI: 10.15430/jcp.2021.26.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Beetroot as a Potential Functional Food for Cancer Chemoprevention, a Narrative Review

Abstract: Patients with cancer are prone to several debilitating effects due to chemotherapy or the disease itself. The behavioural disturbances experienced by patients with cancer include fatigue, insomnia, depression, and cognitive disturbances. These symptoms are very common and may persist for months or years even after completion of treatment and may affect patient's quality of life. Functional foods have long been linked to improve human performance and health, and hence are considered beneficial as part of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 122 publications
1
22
0
1
Order By: Relevance
“…Concerning the soluble solids content, the eggplant sample and its juice showed the lowest value and apples showed the highest. Apples are rich in sucrose and fructose [36] , and beetroot is known as a source of sucrose [40] . Generally, the values of pH and total soluble solids are similar to those previously reported in the literature for the three products [41] , [42] , [43] , [44] , [45] , [46] .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the soluble solids content, the eggplant sample and its juice showed the lowest value and apples showed the highest. Apples are rich in sucrose and fructose [36] , and beetroot is known as a source of sucrose [40] . Generally, the values of pH and total soluble solids are similar to those previously reported in the literature for the three products [41] , [42] , [43] , [44] , [45] , [46] .…”
Section: Resultsmentioning
confidence: 99%
“…Early studies on beetroot juice on DMBA treated rats showed increased activity of phase II enzymes in the liver and mammary gland, indirectly indicating the induction and activation of Nrf2 [ 77 ]. However, beetroot water extracts were not found to induce phase II enzymes in human colon adenocarcinoma cells in vitro [ 78 ]. The protective effect of beetroot juice against rat liver injury and inflammation induced by carcinogenic N-nitrosodiethylamine (NDEA) was also demonstrated.…”
Section: Phytochemicals As Modulators Of Nrf2 and Nf-kb Signaling Pathwaymentioning
confidence: 99%
“…Apart from these carcinogens present in food products, there are some other chemicals present in several food stuffs that are actually beneficial to the human beings [78]. Some of them have immunomodulatory benefits like taro root (Colocasia esculanta) [79], some of them may serve as a functional food for the prevention of cancer like Beetroot (Beta vulgaris), or Capsaicin [80].…”
Section: Some Anti-carcinogenic Food Productsmentioning
confidence: 99%